Desorption of zinc heavy metal ion from soybean waste biosorbent / Sharifah Iziuna Sayed Jamaludin ...[et al.] - Sayed Jamaludin, Sharifah Iziuna; Adlan, Aqil; Mohd Sharawi, Nazifa; Selama, Intan Sharmiela
The study was carried out to measure the effect of type of elution reagents, concentration of elution reagents and contact time with elution reagent on desorption of Zinc (II) heavy metal ions from soybean waste biosorbents. Organic waste like soybean waste contain several functional group like carboxyl, carbonyl, acetamido, amino and hydroxyl. These functional group are contained in natural polymers such as cellulose, hemi-cellulose, pectin and lignin which able to bind heavy metal ions present in aqueous solution. The biosorbent, soybean waste in this research were characterized with Fourier Transform Infrared (FTIR) to identify the characteristic of the soybean waste as an efficient biosorbent. Then, investigation and comparison of the effects of eluent type, eluent concentration and contact time was made for the desorption study of the soybean waste. Desorption experiment was conducted with three different elution with two different concentrations each. (The elution used in this study are HNO3 (0.lM & I.OM), NaOH (0. l M & I.OM) and EDTA (0.05 M & O.l M).) The sample after the desorption study is then tested by running the Inductively Couple Plasma - Optical Emission Spectrometry (ICP-OES) test. The results show that the maximum Zinc (II) ions desorption capacity was 88.43% with the elution of HNO3 at 0.1 M. while the minimum Zinc (II) ions desorption capacity was NaOH at 1.0 M with 28.76% of heavy metal desorption. The results of this study imply that soybean waste is a suitable biomass to remove Zn and are able to under goes the desorption process for regeneration and reusability that is economically beneficial.